PENERAPAN FUZZY ANALITYCAL HIERARCHY PROCESS UNTUK MENENTUKAN PRIORITAS PEMBANGUNAN IRIGASI DI PROVINSI SUMATERA UTARA - Friska Putri Ariyati; Fibri Rakhmawati; Ana Uzla Batubara (LPPM Universitas Bina Bangsa, 2024)
In agriculture, irrigation is important, one of the factors that will ensure agriculture runs well is irrigation. Artificial irrigation can be a solution to this problem, but creating artificial irrigation requires quite a large cost. Therefore, Dinas Tanaman Pangan dan Holtikultura is helping farmers to develop a tertiary plot irrigation network covering an area of less than 1000 hectares. With so many applications coming to the Dinas Tanaman Pangan dan Holtikuoltura, the Fuzzy Analytical Hierarchy Process method could be a solution for determining irrigation development priorities. The results of the analysis used the Fuzzy Analytical Hierarchy Process with the criteria: Irrigation Area, Area of Rice Fields Served by Irrigation, Irrigation Development Costs, and Construction Time and alternatives: Sunggal Irrigation Area, Teluk Mengkudu Irrigation Area, Pantai Cermin Irrigation Area, Medang Deras Irrigation Area, Lima Puluh Pesisir Irrigation Area, Gunung Malela Irrigation Area, Nagori Silulu Irrigation Area, Juhar Irrigation Area, Sayur Matinggi Irrigation Area, Panyabungan Irrigation Area and Panyabungan Barat Irrigation Area, namely the Lima Puluh Pesisir area is ranked first in the priority of irrigation development in North Sumatra with a value of 0.852